Pemberdayaan Masyarakat Melalui Edukasi Pengelolaan Limbah Industri di Pabrik Roti Jordan Bakery Kendari Sulawesi Tenggara - Sitti Rabbani Karimuna; Firdah Julia; Amelia Putri; Cinta Priode Yankes; Bunga Lestari; Ernis Ernis; Gracia Esti Putri; Sri Wahyuni; Karamoi Karamoi; Mila Angraeni; Muh. Fitra Annaba; Wa Ode St. Iqlima Inayah Hibi; Mohammad Syawal; Aweida Kadepa; Reza Audya Rahmawati Himboro; Yusniar Purnama Safar; Yulya Alfaiga; Andi Regita Fernila; Arzul Rahmat Asdar (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Industrial waste management is a crucial aspect of maintaining environmental sustainability and the health of communities around industrial areas. This study aims to empower the community through education on industrial waste management at Jordan Bakery Factory in Kendari, Southeast Sulawesi. The methods used were participatory observation and interviews with the waste management staff at the factory. The results of the community service show that the factory has implemented a good system for managing liquid and solid waste, including a liquid waste filtration process and economic utilization of solid waste. In addition, the service team also prepared educational materials in the form of pamphlets containing information about types of waste, proper management methods, and the environmental impact of waste. This education is expected to increase awareness and participation among the community and factory workers in responsible waste management. This study contributes positively to environmentally friendly and sustainable industrial waste management in the Kendari area